UPAYA DINAS PENGELOLAAN PASAR DAN KEBERSIHAN KABUPATEN BUNGO DALAM MENGATASI TINGGINYA TUNGGAKAN RETRIBUSI DI PASAR BUNGUR KABUPATEN BUNGO - Siti Maryam; Akhmad Legianto (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
The year-end report from the Market Management and Hygiene Service stated that user fees from the market are one of the local revenue sources that generate the most user fees. However, in achieving its realization, it is very difficult to achieve, this can be seen from the receipt of the Bungur Bungur market levy for the last 2 years. Bungur Market retribution collection is not optimal, it can be seen in the table above from 2013-2014 the realization of market retribution in Bungo Regency, especially Bungur Market, has never met the target. The method used in this study is a descriptive method with a qualitative approach. The method used to find informants using